Targeting Tumor-Associated Macrophages for Imaging - Jiahao Hu; Xiaoling Xu; Yongzhong Du (MDPI AG, 2022)
As an important component of the tumor immune microenvironment (TIME), tumor-associated macrophages (TAMs) occupy a significant niche in tumor margin aggregation and respond to changes in the TIME. Thus, targeting TAMs is important for tumor monitoring, surgical guidance and efficacy evaluation. Continuously developing nanoprobes and imaging agents paves the way toward targeting TAMs for precise imaging and diagnosis. This review summarizes the commonly used nanomaterials for TAM targeting imaging probes, including metal-based nanoprobes (iron, manganese, gold, silver), fluorine-19-based nanoprobes, radiolabeled agents, near-infrared fluorescence dyes and ultrasonic nanobubbles. Additionally, the prospects and challenges of designing nanomaterials for imaging and diagnosis (targeting efficiency, pharmacokinetics, and surgery guidance) are described in this review. Notwithstanding, TAM-targeting nanoplatforms provide great potential for imaging, diagnosis and therapy with a greater possibility of clinical transformation.